Effects of Father’s Absence on Child Growth and Development During Early Years - Sana Lakhani, Sanober Nadeem (JECCE, 2023)
Presence of both mother and father are crucial for optimum emotional, spiritual and physical development of children. The main purpose of this study was to explore mother perceptions regarding the effects of father’s absence on child growth and development. The qualitative approach was used to explore this phenomenon with mothers of 1 to 8 years old children, where father was absent since last six months. Two focus group discussions and five In-depth interviews were conducted in three middle class communities of Karachi, Pakistan. Each FGD involved 10 mothers who were recruited through purposive sampling and consented to participate. Findings of the current study have been categorized into four main themes as father's role in child development, Problems mothers face while nurturing their children and the support systems of mothers and family. Study concluded that physical absent of father contributed in negative outcome on child emotional, social, psychological and physical development. Mother experienced stress and depression while handling many responsibilities on everyday lives. Girl child and boy child both suffers equally and need their father presence in social and academic activities and daily life. While making programs for holistic child development policy maker should consider this issue.